Raman study of laser-induced heating effects in free-standing silicon nanocrystals. Issue 18 (14th May 2015) - Han, Lihao; Zeman, Miro; Smets, Arno H. M.
<x xml:space="preserve">Abstract</x> The size-dependent temperatures of free-standing Si nanocrystals under laser illumination are determined by Raman spectroscopy.